Analytic of the Ball Worm Transmission - Li Hanwu (Jixie chuandong)
The performance index to improve the transmission efficiency is discussed,the application prospect of the a new design in mechanical transmission field-ball worm pair with the rolling balls as meshing tooth is analyzed and compared on the technical.The transmission principle of the mechanism is analyzed,and the basic formula of the mechanism design calculation is proposed,and it is showed through the design example for this kind of ball worm pair.